THE APPLICATION OF SHIFT METHOD USING MOVING LASER ON CANCER CASES IN HEAD AREA USING 3DCRT AND VMAT TECHNOLOGY - Samsun Samsun; Nursama Heru Apriantoro; Rudi Kurniawan; Agnes Dwika Septiti (Spektra: Jurnal Fisika dan Aplikasinya, 2019)
The accuracy of patient position is essential to achieve the purpose of radiotherapy. Therefore, before radiotherapy, the isocenter of the patient must be determined to find out the target location. Verification serves to determine the isocenter that shifts from the reference point on the CT simulator. This research was conducted using field observation method, comparing the results of the isocenter after verification with the isocenter on the moving laser. Eight (8) samples from primary data were taken. Shift data was obtained from the average value and standard deviation. The instrument used was a linear accelerator of clinic iX type and On-Board Imager. The results obtained were the average lateral coordinate point of 0.055 cm; at the longitudinal isocenter point of 0.10 cm; and at the vertical isocenter point of 0.053 cm. From this research, it was concluded that the average value o the isocenter shift was less than 0.3 cm. This method can be used because the shift does not exceed the tolerance limit.